Matriz energética atual, transição e perspectivas até 2050: desafios e oportunidades para a neoindustrialização do Nordeste brasileiro a partir das energias renováveis - Fortes, Hailton José (2024)
Promoting the transition to a more sustainable energy matrix must, primarily, be associated with public power management for investment in renewable energy, expanding energy generation capacity and promoting the diversification of the energy matrix. The Brazilian Northeast is a privileged region with great potential for solar and wind energy generation, which allows the creation of opportunities for industrialization and export of surplus production based on these clean energy sources. Given this context, the following guiding question is defined: What are the challenges and opportunities for the industrialization of the Brazilian Northeast, based on the energy transition, with an emphasis on renewable energy? The study's general objective is to analyze the situation of the current energy matrix and identify the challenges and opportunities for the industrialization of the Northeast, based on the energy transition and perspectives until 2050, based on renewable energy. This is a qualitative research, despite the display of quantitative data; Initially, a literature review was carried out on theoretical frameworks related to the current energy matrix, transition and perspectives until 2050, and the opportunities and challenges of exporting and industrializing the Northeast using renewable energy, with secondary data displayed; Subsequently, field research was carried out at Banco do Nordeste, the primary data obtained dealing with the financing demands of green hydrogen and decarbonization projects. It is concluded that, by 2050, the prospects for the energy transition for Brazil are promising, with the expectation of an increase in the share of renewable energy in the energy matrix and the consolidation of the country as a producer and exporter of clean energy, in response to changes climate change and international environmental cooperation agreements, as well as geopolitical factors. With this, opportunities arise for the industrialization of the Northeast, as the questioning of the advantages of the offshoring model, climatic conditions, geographic position, existing infrastructure and structuring of financing lines become attractive for installing industrial plants in the region, with emphasis on production of green hydrogen, which is an input for the others; however, there are relevant challenges regarding strengthening this infrastructure, improving regulatory frameworks and encouraging technological innovation for the production, storage, transport and distribution of clean energy. In this way, it is possible to affirm that the research objectives were achieved.